2017
DOI: 10.3390/nu9070719
|View full text |Cite
|
Sign up to set email alerts
|

Acute Supplementation with High Dose Vitamin D3 Increases Serum Anti-Müllerian Hormone in Young Women

Abstract: Anti-Müllerian hormone (AMH) is a paracrine regulator of ovarian follicles. Vitamin D (Vit D) regulates AMH production in vitro, but its role as a regulator of ovarian AMH production is contentious. If Vit D influences ovarian AMH production, then an acute rise in Vit D level should lead to an acute rise in circulating AMH levels. This hypothesis was tested with a randomized double-blind design, with 18–25-year-old women recruited from the community. The study was conducted in early spring, when the marker of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 21 publications
2
41
1
4
Order By: Relevance
“…Limitations of this study include its relatively small female population size, as well as the possibility that the observed decline in AMH was related to natural aging (over six months) rather than a seasonal variability in vitamin D levels between summer to winter. The same investigators subsequently conducted a randomized double-blind clinical trial in young women (18-25 years old) with regular menstrual cycles recruited from the community to evaluate the effects of an acute rise of vitamin D on systemic AMH levels over a one-week period [62]. The study was conducted in the early spring when vitamin D levels tend to be at their nadir.…”
Section: Interventional Studiesmentioning
confidence: 99%
“…Limitations of this study include its relatively small female population size, as well as the possibility that the observed decline in AMH was related to natural aging (over six months) rather than a seasonal variability in vitamin D levels between summer to winter. The same investigators subsequently conducted a randomized double-blind clinical trial in young women (18-25 years old) with regular menstrual cycles recruited from the community to evaluate the effects of an acute rise of vitamin D on systemic AMH levels over a one-week period [62]. The study was conducted in the early spring when vitamin D levels tend to be at their nadir.…”
Section: Interventional Studiesmentioning
confidence: 99%
“…Dennis et al also showed that both 25(OH) D and AMH exhibited seasonal variations in women with a fall of AMH in winter and this seasonal drop in AMH level can be prevented by cholecalciferol supplementation. Recently, serum AMH level is found to be increased after vitamin D supplementation in a group of early reproductive women . In contrary, a retrospective study by Pearce et al on 340 infertile women (58 had PCOS and 282 were ovulatory) failed to demonstrate any seasonal fluctuation of serum AMH with vitamin D status in either the PCOS or ovulatory subgroups.…”
Section: Discussionmentioning
confidence: 94%
“…18,19 Recently, serum AMH level is found to be increased after vitamin D supplementation. 20 If a clear relationship is confirmed between vitamin D and AMH, it can lead to a better understanding of the pathophysiology of PCOS and prompt novel potential treatments of anovulation secondary to PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of supplementation of vitamin D3 and AMH levels, Dennis et al, randomized 49 patients to 50,000 IU of vitamin D3 or placebo. They found that AMH levels rose by 12.9% over 7 days in the treated group suggesting an effect on ovarian reserve (Dennis et al, 2017).…”
Section: Vitamin D Supplementationmentioning
confidence: 96%